A Depth-First Search Algorithm for Optimizing the Gravity Pipe Networks Layout - Rodrigues, Gustavo Paiva Weyne; Costa, Luis Henrique Magalhães; Farias, Guilherme Marques; de Castro, Marco Aurélio Holanda (Water resources management, 2019)
The layout is displayed in one of the most complex tasks in the gravity pipe network project because there are several factors to consider and often a choice of unassociated or smaller layout. Currently, the designer’s experience is needed so different layout alternatives be analyzed to reduce the depths of the network. Generally, this operation is manual and does not ensure the best result. For this research, a depth-first search algorithm was presented, which allows the optimization of the layout of a gravity pipe network, assessing the topographic conditions of the manholes (nodes), leading to a layout that has the sum of lower unfavorable slopes. A hypothetical and a real network were used. The computational time required was considered negligible. The results showed a robust model, which works for the complete layout of any network, of any size, resulting in the lowest possible depths.